ANALYSIS OF THE IMPLEMENTATION OF KNOWLEDGE SHARING VIA FACEBOOK MEDIA IN THE LIBRARIAN WRITING CLASS COMMUNITY - Anggara, Widya Tri Dewi (Academic Solution Publisher, 2024)
This research is aimed to recognize hos knowledge sharing is applied through facebook in a KMP. The method used in this research is qualitative method with case study approach. The data collection technique is done through observation, indepth-interview and study of documentation. The informant is choosed by the purposive sampling technique. The result of this research shows that knowledge sharing applied through facebook in the librarian creative class based on the theory of Nonaka and Takeuchi involves the process of socialization, externalization, combination and internalization. The process of socialization done in the KMP community is recognized by the existence of incidental meeting activity and sharing activity infacebook group. Generally, the process of externalization done in the KMP community can be seen when someone is in charged of writing the result of documentations in the KMP. They are soft copy, hard copy,and also pictures from the meeting. The process of combination done by the KMP community is to deliver the result ofdocumentation in the facebook group. The combination of knowledge resulted from the sharing session is combined with the knowledge resulted from the meeting, then it is combined again with the knowledge resulted from the internet or journals. The process of internalization done in the community of KMP is to apply and share the knowledge they have from their learning and experience to the others.